The mediating effect of changes in hand impairments on hand function in patients with rheumatoid arthritis: exploring the mechanisms of an effective exercise programme - Hall, A; Copsey, B; Williams, M; Srikesavan, C; Lamb, S (Wiley, 2016)
Objective: To determine whether the effect of the ‘Strengthening And stretching for Rheumatoid Arthritis of the Hand’ (SARAH) exercise programme on hand function was mediated by changes in the proposed active ingredients: strength, dexterity, and/or range of motion. Methods: The SARAH intervention included exercises hypothesized to improve potential mediators of grip strength, pinch strength, wrist flexion, wrist extension, finger flexion, finger extension, thumb opposition, and dexterity, which would theoretically improve self-reported hand function. All variables were measured at baseline and at 4 and 12 months. Structural equation modelling was used to assess mediation on change in hand function via change in potential mediators. Results: Change in grip strength partially mediated change in hand function. Grip strength mediated 19.4% (95% confidence interval: 0.9% to 37.8%) of the treatment effect. Discussion: Improvements in grip strength at 4 months are likely to mediate improved hand function at 12 months. The role of joint mobility exercises is less clear and is likely influenced by the choice of measurement tools for both mobility and function outcomes. More robust measurements of wrist and hand mobility for patients with rheumatoid arthritis may be necessary to determine the relationship between this variable and self-reported hand function. Conclusion: Using a large trial dataset, we have demonstrated that techniques used to target grip strength are key active ingredients of the SARAH exercise programme and mediate its effect.